Pulmonary vein capture is a predictor for long-term success of stand-alone pulmonary vein isolation with cryoballoon ablation in patients with persistent atrial fibrillation - Babak, Alexey; Kauffman, Christine Bienvenue; Lynady, Cynthia; McClellan, Reginald; Venkatachalam, Kalpathi; Kusumoto, Fred (Frontiers in Cardiovascular Medicine, 2024)
The mechanisms of AF development and progression are still not completely understood.14 Despite the relative efficacy of ablation, the risk of AF recurrence is substantial, particularly in patients 15 with persistent AF (perAF) [1,2]. 1,2 At present we do not have any reliable intra-procedural electrophysiologic 16 predictors of long-term success of AF ablation other than pulmonary vein isolation. We evaluated selected 17 intraprocedural pulmonary vein characteristics that may be helpful in future guidance of persistent AF ablation.18 Methods: 390 consecutive procedures using cryoballoon for initial AF ablation were divided by clinical 19 presentation (paroxysmal or persistent AF), and by pulmonary vein (PV) response to pacing after completion 20 of ablation (discrete electrogram elicited with pacing -"PV capture" or not -"Control"). Patients were followed 21 (median 20 months) for recurrent atrial arrhythmias as the primary end point of the study.Results: PV capture was identified in 20.3% and 17.1% and patients with paroxysmal and persistent AF 23 respectively (ns). In patients with persistent AF presence of PV capture was associated with significantly better 24 outcomes compared to patients without PV capture (p < 0.001). In the group "persistent AF and PV capture", an 25 initial strategy of PV isolation and reisolation of the PVs (without additional lesions) for patients with recurrent 26 atrial arrhythmias resulted in 20/23 (87%) patients in sinus rhythm off antiarrhythmic medications at study com-27 pletion. In patients with paroxysmal AF, PV capture was not associated with outcome benefits. Specific electro-28 physiologic characteristics of PV (PV capture cycle length: PVCCL) did not have an impact on AF recurrence, 29 although 25% shortening of PVCCL was observed after 60 second periods of pacing at short cycle lengths. No 30 background demographic patient characteristic differences were identified between patients with vs without PV 31 capture.The presence of PV capture was associated with better outcomes in patients with persistent AF. 33 PV capture may identify those patients with persistent AF in whom cryoballoon PV isolation alone is sufficient 34 as an initial ablation procedure and as the primary ablation strategy for recurrent AF.